Maternal and Neonatal Outcomes in Pregnant Women Presented with or Without COVID-19 Disease (Medical Forum Monthly, 2021)
Objective: To compare the maternal and neonatal outcomes in patients with or without coronavirus disease.Study Design: Prospective/observational studyPlace and Duration of Study: This study was conducted at the Obstetrics & Gynaecology department, Liaquat College of Medicine and Dentistry Darul Sehat Hospital, Karachi for duration of six months April, 2020 to September, 2020.Materials and Methods: One hundred eighty patients with ages 18 to 35 years and gestation age >24 weeks were included. Patient’s demographical detail including age, residence, education and socioeconomic status were recorded. All the patients were divided into two groups; Group A consists of 90 patients presented with COVID-19 and Group B with 90 patients without COVID-19. Maternal outcomes were recorded. Neonatal outcomes such as admission to NICU, birth weight, Apgar score and mortality were recorded.Results: There were no significant difference in term of age between Group A and B 28.5 years and 28.76 years. Mean BMI in group A was 25.85±2.65 kg/m2 and in group B it was 26.89±2.48 kg/m2.In group A frequency of C-section was higher 56 (62.22%) and in group B it was 24 (26.7%). Frequency of preterm in group A was 22 (24.44%) while in group B was 10 (11.11%). In Group A 33.3% neonates need to NICU. Low birth weight was 26 (28.89%) higher in Group A patients. 4.44% neonatal death was recorded in Group A while none in Group B.Conclusion: The pregnant women with COVID-19 disease had more complications and higher rate of lower segment cesarean section and preterm delivery as compared to normal pregnant women.